Strengthening of the Brazilian Agricultural Protection System. Developmente of the Agricultural Managemente Platform (PGA) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
4 pages